2020
DOI: 10.12890/2020_001701
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pericarditis and Cardiac Tamponade in a Patient with COVID-19: A Therapeutic Challenge

Abstract: We report a case of acute viral pericarditis and cardiac tamponade in a patient with COVID-19 to highlight the associated treatment challenges, especially given the uncertainty associated with the safety of standard treatment. We also discuss complications associated with delayed diagnosis in patients who potentially may need mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Pericarditis has been noted to be a rare presenting symptom of COVID-19, occurring at the time of or shortly after diagnosis [12][13][14]. Pericarditis and myocarditis presentations associated with positive COVID-19 PCR testing have ranged in reported acuity from mild symptoms to lethal tamponade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pericarditis has been noted to be a rare presenting symptom of COVID-19, occurring at the time of or shortly after diagnosis [12][13][14]. Pericarditis and myocarditis presentations associated with positive COVID-19 PCR testing have ranged in reported acuity from mild symptoms to lethal tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…This case is notable in its subtle presentation, EKG and echocardiogram findings, which required multiple evaluations prior to definitive diagnosis. Early diagnosis of pericarditis is essential as it is known complications include constrictive pericarditis and cardiac tamponade, with life-threatening presentations previously described in the setting of COVID-19 [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases present acutely at the time of diagnosis and up to 2 weeks after the first positive COVID-19 test. 3 7–10 14–19 There are no clear common risk factors for those who developed symptomatic acute pericarditis. Some had cardiovascular disease including recent myocardial infarctions, but many were healthy or had controlled chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Most cases progress to a chronic disease requiring surgical intervention with pericardiectomy—the surgical removal of both the parietal and epicardial layers of the pericardium—as the only definitive treatment. 3 One study found that 17% of CP cases resolved without surgery after about 8 weeks of medical therapy alone. However, most cases progressed to a chronic disease requiring definitive treatment with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%